PENGGUNAAN METODE STATISTIK DALAM PERUMUSAN STRATEGI PEMASARAN PRODUK BERDASARKAN PREFERENSI DAN PERSEPSI KONSUMEN - Julius Kurata; Patdono Suwignjo (Lembaga Penelitian dan Pengabdian kepada Masyarakat- Institut Teknologi Sepuluh Nopember, 2005)
Three components of marketing strategies are segmentation, targeting, and positioning. Increasingly tight market competition compels a more accurate formulation of the three components of marketing strategy. The knowledge of consumer’s preferences and consumer’s perception about a product’s main competitors will help the formulation of marketing strategy. The use of more quantitative statistic methods i.e. cluster analysis and crosstab analysis are expected to give more exact results in order to give more accurate steps of marketing strategy formulation.